Novel Reviews. Issue 2 (1st December 2020) - Molloy, Deborah Snow; Briwa, Robert M.
Abstract : Ann Petry, The Street (London: Virago, 2019), 416pp., £9.99 (soft back) Luis Alberto Urrea, The Devil's Highway: A True Story (New York: Little, Brown and Company, 2004), xxi +239 pp. $16.99 (paperback).